Physicochemical characterization of bioactive compounds in nanocarriers - Barros, Rafaella Moreno; de Oliveira, Maísa Soares; Costa, Kammila Martins Nicolau; Sato, Mariana Rillo [UNESP]; Santos, Karen Loraine Macena; Damasceno, Bolívar Ponciano Goulart de Lima; Cuberes, Teresa; Oshiro-Junior, João Augusto (Bentham Science Publishers, 2020)
The encapsulation of bioactive compounds is an emerging technique for finding new medicines since it provides protection against ambient degradation factors before reaching the target site. Nanotechnology provides new methods for encapsulating bioactive compounds and for drug carrier development. Nanocarriers satisfactorily impact the absorption, distribution, metabolism, and excretion rate when compared to conventional carriers. The nanocarrier material needs to be compatible and bind to the drug and be bio-resorbable. In this context, the physicochemical characterization of encapsulated bioactive compounds is fundamental to guarantee the quality, reproducibility, and safety of the final pharmaceutical product. In this review, we present the physicochemical techniques most used today by researchers to characterize bioactive compounds in nanocarriers and the main information provided by each technique, such as morphology, size, degree of crystallinity, long-term stability, the efficacy of drug encapsulation, and the amount released as a function of time.
Keywords: Biological activity; Isolated compounds; Nanoparticles; Nanotechnology